Response of soybean (Glycine max) to molybdenum application in Nigeria - AGHATISE, V O; TAYO, T O (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during 1990 and 1991 to evaluate the optimum rate of molybdenum fertilizer and effect of molybdenum on the growth and yield of soybean [Glycine max (L.) Merr.]. Ammonium molybdate containing 54.3% molybdenum was applied @ 0. 0.2, 0.4 and 0.8 kg/ha.Molybdenum application significantly increased the leaf number and area. plant height, number of branches and nodes compared with the control plants. At 10 weeks after emergence (peak of vegetative growth) Mo application @ 0. 0.2. 0,4 and 0.8 kg/ha gave 11.7, 11.9, 13.4 and 12. leaves: 120.5, 124.4, 143.5 and 117.4 cm2 area; 23.1, 24.2. 25.1 and 24.4 cm height; 3.1.3,3,3.6 and 3.6 branches: 9.8, 10.0, 10.4 and 10.2 nodes respectively. It also significantly increased the dry weight of leaves. stem and nodules. and the total dry weight compared with the control plants. At 12 weeks after emergence, application of 0. 0.2. 0,4 and 0,8kg Mo/ha gave respectively 0.74,0.79.0.85 and 0.65 g dry weight of leaves; 0.8. 0.90. 0.93 and 0.79 g dryÂ  weight of stem; 0.001, 0.013,0.030 and 0.003 g dry weight of nodules: and 3.4,4,1.4.0 and 3.5 g total dry weight. Molybdenum @ 0.2 and 0.4 kg/ha gave significantly higher dry weight of pods. ie 2.9 and 2.5 g, respectively. The total and functional pods were significantly increased by the Mo treatment compared With control Mo @ 0.0.2. 0.4 and 0.8 kg/ha gave 9.2. 12.3. 12.0 and 9.B pods and6.5. 9.2, 8.5 and 7.3 functional pods respectivety. There was no consistent significant effect of Mo on absolute growth, retative growth. net assimilation rate and leaf: area ratio compared with the control plants. At final harvest, Mo @ 0.2 and 0.4 kg/ha increased the dry weight of seeds by 29 and 10% respectively compared with the control. The improvement in the growth and yield of soybean due to Mo fertilization was perhaps owing to the increased N fixation and nitrate reduction by the plant.